The effects of increased distance travel on the operating costs of freight truck vehicles - Siti Aishah Hadawiah Ahmad; Mohd Nizam Ab Rahman; Rizauddin Ramli; Ariff Azly Muhamed (Penerbit Universiti Kebangsaan Malaysia, 2024)
Transportation industry is an important part of most countries’ economies with significant effects on productivity and social welfare. However, refrigeration has dramatically altered global food transportation efficiencies in the cold supply chain. Hence, a key factor to optimize transportation is by lowering operational costs, with distance travel having a considerable impact. The paper examines how the operational costs of different truck classes is influenced by the distance travelled. The operating cost equation was utilized to make a comparison between vehicle operating costs and to assess how these costs change in relation to travel distance. The equation consists of influential parameters such as fuel cost, driver wage, and maintenance cost of a vehicle. The result showed that the operating cost rate varies among trucks of different classes. According to the results of the equation and effective parameter analysis, 18-ton trucks had the highest cost, followed by 5-ton trucks. This is due to fact that the cost is influenced by factors of travel distance, tolls, and fuel consumption. Furthermore, based on transportation costs, a green practice framework can be constructed to reduce truck costs for each delivery while reducing CO2 emissions to the environment. By taking into account transportation cost factors in the framework of green practices, effective and practical information can be generated such as product delivery schedules to customers and better routes to improve business performance. Finally, effective transportation management can improve inventory flow by enhancing warehouse efficiency, reducing overall lead time, and saving on storage costs.